Հարկային ռազմավարության տեղը պետական կառավարման համակարգում - Սուրիկ Նաիրիի Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Концепция стратегического управления получила широкое распространение в экономике с 50-х годов прошлого века в области корпоративного управления западных стран. The concept of strategic management has become widespread in the Economics since the 1950s of the last century in the field of corporate governance of the Western countries.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ